Hybrid Surgery of Multilevel Cervical Degenerative Disc Disease : Review of Literature and Clinical Results - Lee, Sang-Bok (The Korean Neurosurgical Society, 2012)
OBJECTIVE: In the present study, we evaluated the effect, safety and radiological outcomes of cervical hybrid surgery (cervical disc prosthesis replacement at one level, and interbody fusion at the other level) on the multilevel cervical degenerative disc disease (DDD). METHODS: Fifty-one patients (mean age 46.7 years) with symptomatic multilevel cervical spondylosis were treated using hybrid surgery (HS). Clinical [neck disability index (NDI) and Visual Analogue Scale (VAS) score] and radiologic outcomes [range of motion (ROM) for cervical spine, adjacent segment and arthroplasty level] were evaluated at routine postoperative intervals of 1, 6, 12, 24 months. Review of other similar studies that examined the HS in multilevel cervical DDD was performed. RESULTS: Out of 51 patients, 41 patients received 2 level hybrid surgery and 10 patients received 3 level hybrid surgery. The NDI and VAS score were significantly decreased during the follow up periods (p<0.05). The cervical ROM was recovered at 6 and 12 month postoperatively and the mean ROM of inferior adjacent segment was significantly larger than that of superior adjacent segments after surgery. The ROM of the arthoplasty level was preserved well during the follow up periods. No surgical and device related complications were observed. CONCLUSION: Hybrid surgery is a safe and effective alternative to fusion for the management of multilevel cervical spondylosis.